2018
DOI: 10.15171/apb.2018.011
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Isolated from Sewage Eliminates and Prevents the Establishment of Escherichia Coli Biofilm

Abstract: Purpose: Biofilm growth exerts a negative impact on industry and health, necessitating the development of strategies to control. The objective of this work was study the lytic activity of the phage isolated from the sewage network in the formation and degradation of Escherichia coli biofilms.Methods: E. coli cultures were incubated in 96-well polystyrene microplates under controlled conditions to evaluate the biofilm formation. The E. coli cultures and established biofilms were treated with the suspensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…In principle under static conditions, the released progeny will attach to the neighboring bacteria within the biofilms, whereas in case of dynamic conditions, the progeny of virus can target and lyse the entire span of bacterial colonies within the biofilms because of agitation in the experimental setup (Azeredo and Sutherland, 2008; Sillankorva et al, 2010; Azeredo and Sillankorva, 2018). We observed that K. pneumoniae and E. coli showed a significantly higher number of cells as compared to P. aeruginosa and S. aureus under DR condition at 48 h of incubation; Under SR condition, significant growth of MDR-bacterial isolates exhibited successful colonization These observations are in correlation with previous studies (Hughes et al2010; Ribeiro et al, 2018). While in the case of single-species biofilm formed by S. aureus and treated with phage (vB_SAnS_SADP1), we noticed degraded biofilm with some single coccus spread on the coverslip.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In principle under static conditions, the released progeny will attach to the neighboring bacteria within the biofilms, whereas in case of dynamic conditions, the progeny of virus can target and lyse the entire span of bacterial colonies within the biofilms because of agitation in the experimental setup (Azeredo and Sutherland, 2008; Sillankorva et al, 2010; Azeredo and Sillankorva, 2018). We observed that K. pneumoniae and E. coli showed a significantly higher number of cells as compared to P. aeruginosa and S. aureus under DR condition at 48 h of incubation; Under SR condition, significant growth of MDR-bacterial isolates exhibited successful colonization These observations are in correlation with previous studies (Hughes et al2010; Ribeiro et al, 2018). While in the case of single-species biofilm formed by S. aureus and treated with phage (vB_SAnS_SADP1), we noticed degraded biofilm with some single coccus spread on the coverslip.…”
Section: Discussionsupporting
confidence: 92%
“…The biofilms coated on glass slides were fixed with glutaraldehyde (2.5%) and dehydrated through a series of graded ethanol (30-100%) for 5 minutes. Further, the glass slides were sputtered with gold after critical point drying, and the aggregated biofilms were examined using Scanning electron microscopy (FEI, Tecnai G-2S Twin) (Ceri et al, 1999; Ribeiro et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, all the isolated bacteriophages were isolated from sewage Figure 2. Ribeiro et al (2018) could successfully isolate bacteriophages from sewage. They revealed that to the sewage rich contents of bacteria and organic matters.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages lytic against other types of bacteria such as Pseudomonas aeruginosa 25 , Escherichia coli 26 and Streptococcus mutans 27 have been shown to be able to disrupt mono-biofilms formed by their respective hosts. The potential exists for use of bacteriophages against biofilms in periodontal infection 18,19 and colon cancer.…”
Section: Introductionmentioning
confidence: 99%